2013
DOI: 10.1007/s11916-013-0378-z
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channels and Osteoarthritic Pain: Potential for Novel Analgesics

Abstract: Osteoarthritis (OA) is a debilitating chronic condition widely prevalent in ageing populations. Because the pathology of the disease includes cartilage erosion and joint remodelling, OA patients experience a great deal of pain. Despite numerous studies, details of OA are frequently inseparable from other types of chronic pain, and its causes are unknown. In most circumstances in OA, the cartilage lacks afferent innervation, although other joint tissues contain nociceptive neurones. In addition to physical join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 107 publications
2
22
0
Order By: Relevance
“…The pain control and anti-inflammtory are crucial for the treatment of osteoarthritis (Pelletier, Fernandes, Jovanovic, Reboul, & Martel-Pelletier, 2001a). Studies revealed that P2X7 receptor is closely related to the occurence of pain and inflammtory response (Staunton, Lewis, & Barrett-Jolley, 2013).…”
Section: P2x7 Receptor May Aggravate the Process Of Osteoarthritismentioning
confidence: 99%
“…The pain control and anti-inflammtory are crucial for the treatment of osteoarthritis (Pelletier, Fernandes, Jovanovic, Reboul, & Martel-Pelletier, 2001a). Studies revealed that P2X7 receptor is closely related to the occurence of pain and inflammtory response (Staunton, Lewis, & Barrett-Jolley, 2013).…”
Section: P2x7 Receptor May Aggravate the Process Of Osteoarthritismentioning
confidence: 99%
“…As is well known, the purinergic membrane receptor superfamily may be divided into the P1 and P2 receptor families. The P2 family, which can be further divided into the P2X and P2Y subtypes, is closely related to OA-induced pain (11,12). Importantly, a previous study reported that P2 receptor signaling is altered in OA, and that it is associated with an elevated ATP level (12).…”
Section: Introductionmentioning
confidence: 99%
“…This clinical target of Na v 1.7 in osteoarthritis pain is supported by the reported knockout studies and additional literature. 9,19,20 The chiral bicycle 48 was also prepared starting with 39 and using commercially available α-methylbenzyl analog 43 in the presence of catalytic TFA to give an approximate 1:1 mixture of isomers 44 and 45 which was separated via silica gel chromatography (Scheme 7). The resulting single enantiomer 45 next underwent Boc-removal in the presence of excess TFA and the resulting lactam was coupled with indazole bromide 21 using CuI-Buchwald conditions to give 46.…”
Section: Introductionmentioning
confidence: 99%